METHODS OF USING MANAGEMENT ACCOUNTING AND THEIR IMPACT ON INCREASING INVESTORS' CONFIDENCE IN IRAQI JOINT STOCK COMPANIES (World Economics and Finance Bulletin, 2026)
This article aims to clarify the methods and approaches used by management accounting and their impact on the decisions of investors in Iraqi joint stock companies and the extent of financial and accounting disclosure by those companies of accounting information in their financial lists Also, the extent of the commitment of the joint stock companies to apply the budgets whether they are planning balances or capital balances, use of scientific rules and bases, follow-up and control of their results through negative deviations or positive deviations between the planning budgets and the actual results related to profits, revenues and expenses, and indicate the reasons for them by analyzing the results of the accounting system and evaluating performance. This article aims to clarify the methods and approaches used by management accounting and their impact on the decisions of investors in Iraqi joint stock companies and the extent of financial and accounting disclosure by those companies of accounting information in their financial lists Also, the extent of the commitment of the joint stock companies to apply the budgets whether they are planning balances or capital balances, use of scientific rules and bases, follow-up and control of their results through negative deviations or positive deviations between the planning budgets and the actual results related to profits, revenues and expenses, and indicate the reasons for them by analyzing the results of the accounting system and evaluating performance